Implementation of STEM Problem Based Learning Model with Quizizz and iSpring Media Towards Student Learning Outcomes in Stoichiometry Material - Azizah, Meilani; Simangunsong, Garvin; Simamora, Putri Elsa; Juwita, Intan; Manalu, Santa Maria; Simanullang, Tasya Putri Haren; Purba, Jamalum (Universitas Lampung, 2024)
This study aims to determine the significant differences in student learning outcomes using Quizizz Media and i-Spring Media with the STEM Problem Based Learning model on Stoichiometry material. The population in this study were students of class XI IPA at SMA Swata Sultan Iskandar Muda Meda which were divided into four classes. The research sample was students of class XI IPA selected using random cluster sampling techniques. The instrument used in this study was a test with 20 multiple choice questions. The data collected were in the form of student learning outcome ability test instruments. The results of the study were that there was a significant difference between student learning outcomes taught with the STEM-based Problem Based Learning model using Quizizz media with iSpring media with a Sig. (2-tailed) value of 0.001 ≤ 0.05.Keywords: Quizziz, iSpring, and Problem Based Learning.DOI: 10.23960/jppk.v13.i3.32334